TDPAC investigation on thermally related HfF<SU>4.3H2O and HfO2 - Caracoche, María Cristina (1985)
The hyperfine quadrupole interaction of HfF4.3H2O at Hf sites is investigated from 14 to 820 K. No transitions have been found. After the complete dehydration of this compound at 393 K, chemical reactions take place which give rise to hafnium oxifluorides and metastable forms of hafnium oxide. Heating treatments at increasing temperatures make HfO2 turn into its monoclinic phase.